The Image of Muslim/Arab Women on the Front Covers of Literary Works - Al-Matrafi, Huda (International Journal of Language and Literary Studies, 2023)
In several literary works, the images of Muslim/Arab women have increased since the second half of the twentieth century, particularly in art. While exploring the front covers of literary books, one can observe that the ‘Saving Muslim Women’ motif is extremely common. An analysis is made of how popular fiction and non-fiction front covers show Muslim/Arab women’s bodies hidden behind veils, most of which focus on a common theme – the social identity of these women. This paper introduces how the representation of these covered women in veils has become a common trend that is used as stigmatization tools to present what is assumed to be the true image of Muslim/Arab women. In fact, that image continues to be stagnated or stereotyped in both Arab and Western literature. A broad range of sources has been examined to critically explore the images of these women on the front covers of literary works and to understand how stereotyped images have been used to represent them.